Motives and work ethics of street verdors in Kaballokang Pakkabba Village - Rahman, Abdul (Rayhan Intermedia, 2025)
This study aims to determine the reasons for choosing, motives and work ethics as well as the impact of street vendors in Kaballokang Pakkabba Village. This study used in-depth interview techniques, observation, and documentation. The results of the study indicate that: the reasons street vendors choose to trade include, because it does not require large capital, population density and strategic location. The motives of street vendors are the necessities of life and the Islamic work ethic of street vendors is evident from the attitude and understanding of religion in themselves. There are impacts of street vendors, namely providing employment for the community, reducing poverty levels, providing convenience in preparing kitchen spices and various kinds of food for housewives who do not want the hassle As well as convenience for lower-class people to meet their needs with their merchandise offered relatively cheap. As for the negative impact, the presence of street vendors creates noise during break time